Early evidence for bear exploitation during MIS 9 from the site of Schöningen 12 (Germany). Issue 177 (April 2023) - Verheijen, Ivo; Starkovich, Britt M.; Serangeli, Jordi; van Kolfschoten, Thijs; Conard, Nicholas J.
Abstract: A cutmarked bear metatarsal and phalanx from the German open-air sites of Schöningen 12 II-1 and 12 B, respectively, correlated with the interglacial optimum of MIS 9 (ca. 320 ka), provide early evidence for the exploitation of bear skins. Archaeological sites with evidence of bear exploitation from the Lower Paleolithic are rare, with only Boxgrove (United Kingdom) and Bilzingsleben (Germany) yielding cutmarked bear bones indicating skinning. We interpret these finds as evidence for bear hunting and primary access since bear skins are best extracted shortly after the animal's death. The very thin cutmarks found on the Schöningen specimens indicate delicate butchering and show similarities in butchery patterns to bears from other Paleolithic sites. The Eurasian Lower Paleolithic record does not show any evidence for the exploitation of bear meat; only Middle Paleolithic sites, such as Biache-Saint-Vaast (France; ca. 175 ka) and Taubach (Germany; ca. 120 ka), yield evidence for the exploitation of both skin and meat from bear carcasses. Bear skins have high insulating properties and might have played a role in the adaptations of Middle Pleistocene hominins to the cold and harsh winter conditions of Northwestern Europe.